p? do you mean √?
√(b^2+a^2) = √c^2
clearly the next step is flawed.
√(b^2+a^2) ≠ b+a
while √(b^2*a^2) = √b^2 * √a^2,
√(b^2+a^2) ≠ √b^2 + √a^2
I figure you can take it from there
A student is asked to solve b2 + a2 = c2 for a and gives the following solution. Assume all variables represent positive Real Numbers.
b2 + a2 = c2
pb2 + a2 = pc2
b + a = c
a = c-b
Explain the mistake(s) made by the student and provide the correct solution.
2 answers
a^2+b^2=c^2
a^2=c^2-b^2
a=square root of (c^2-b^2)
a^2=c^2-b^2
a=square root of (c^2-b^2)